Electron-immunocytochemical studies of perivascular nerves of mesenteric and renal arteries of golden hamsters during and after arousal from hibernation - SAITONGDEE, PORNCHARN (1999)
Electron immunocytochemistry was used to examine perivascular nerves of hamster mesenteric and renal arteries during hibernation and 2 h after arousal from hibernation. Vessels from cold-exposed but nonhibernating, and normothermic control hamsters were also examined. During hibernation the percentage of axon profiles in mesenteric and renal arteries that were immunopositive for markers of sympathetic nerves, tyrosine hydroxylase (TH) and neuropeptide Y (NPY), were increased 2–3 fold compared with normothermic and cold control animals. This increase was reduced markedly only 2 h after arousal from hibernation. The small percentage of nitric oxide synthase-1-positive axon profiles found in mesenteric (but not renal) arteries was also increased during hibernation and returned towards control values after arousal. In contrast, the percentage of perivascular axons immunostaining for vasoactive intestinal polypeptide (VIP), a marker for parasympathetic nerves, was reduced in mesenteric arteries during hibernation. There was no labelling of perivascular nerves for substance P in either mesenteric or renal arteries. It is suggested that the increase in percentage of TH- and NPY-immunostained perivascular nerves may account for the increased vasoconstriction associated with high vascular resistance that is known to occur during hibernation. The reduction in the percentage of axons positive for VIP in hibernating animals would contribute to this mechanism since this neuropeptide is a vasodilator.